Status of Gastric Mucosa and Liver in Mice upon Treatment with Diclofenac Sodium - Hoque, Nazmul; Islam, Md Kamrul; Islam, Md Monirul; Chowdhury, Md Mustafizur Rahman; Rahman, Md Mizanur (Journal of Bangladesh Society of Physiologist, 2011)
Background: Diclofenac sodium is a non-steroidal anti-inflammatory drug with reportedly undesirable harmful side effects including blood disorders, abdominal pain, ulceration and bleeding of the stomach or intestine. Objective:The present study was conducted to investigate the effect of diclofenac sodium on erythropoiesis, on stomach and liver under different conditions. Method: This experimental study on animal model was conducted in the Department of Physiology, Bangladesh Agricultural University, Mymensingh, between July and August 2007. A total of 45 Swiss Albino mice were randomly assigned into five equal groups (n=9) and they all were fed with standard broiler pellet (25 gm/mice/day) throughout the experimental period of 40 days. Keeping 1 group as control(groupA), 4 groups were treated with diclofenac sodium @ 3 mg/kg body weight (bwt) orally in empty (group B)or full stomach with (group c) or without vitamin B12 (group D) @ 10 μg/Kg body weight through intramuscular route. Total erythrocyte count (TEC) and Hb% was determined to assess erythropoiesis. Macroscopic and microscopic changes of liver and stomach were studied by standard laboratory method. Data were analyzed statistically by ANOVA and un paired t test. Result: Oral administration of this drug significantly (p<0.01) decreased Total Erythrocyte Count(TEC) and Hb in the animals treated with diclofenac sodium in empty stomach and in the animals treated with diclofenac sodium plus vitamin B12 in empty stomach. All the treated mice showed slight to moderate congestion of the gastric mucosa and liver. Conclusion: Intake of diclofenac sodium in empty stomach may produce harmful side effect on stomach and liver. Key words: Stomach; Mice; Diclofenac sodium. DOI: 10.3329/jbsp.v5i2.6783 J Bangladesh Soc Physiol. 2010 December; 5(2): 89-93